The Role of Professional Ethics of Auditors in Maintaining the Credibility of Financial Statements and Public Trust - Daulay, Badriah; Muharrammaini, Ulfa; Azzahra, Fathonah; Sembiring, Egia Mintania Sri Rezeki; Damayanti, Asty Tyty; Sitompul, Gress; Darma, Dito Aditia (CV Raskha Media Group, 2025)
Professional ethics of auditors are the main foundation in maintaining the quality of audits and the credibility of financial statements. Financial statements used as the basis for economic decision- making require an objective, independent, and integrity audit process. This article aims to analyze the ethical role of the auditor profession in maintaining public confidence in financial statements. The methods used are literature studies on auditing textbooks, professional codes of ethics (KEPAP and IESBA), Professional Standards for Public Accountants (SPAP), as well as cases of auditor ethics violations in Indonesia and internationally. The results of the study show that integrity, independence, professional competence, and professional skepticism are the main ethical principles that have a significant effect on audit quality and the level of public trust. Strengthening ethical culture, regulatory supervision, and continuous professional education are important strategies in maintaining the credibility of the auditor profession.